Motivators and Hygiene Factors in Employee Retention: Insights from Herzberg Theory - Shinde, Shilpa (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
Employee turnover presents a significant challenge to organizations globally, impacting costs, productivity, and overall organizational health. Understanding the psychological drivers of retention is critical for developing effective strategies to mitigate turnover. This research explores Herzberg’s Two-Factor Theory as a predictive framework for employee turnover and retention, emphasizing the distinct roles of motivators and hygiene factors. Motivators, including achievement, recognition, responsibility, and growth, drive job satisfaction and foster employee commitment, while hygiene factors such as salary, job security, policies, and working conditions primarily prevent dissatisfaction and turnover. The study highlights the interplay between these factors and their differential impact on retention behaviour, supported by industry-specific examples from IT, healthcare, and education sectors, with particular attention to the Indian context. Challenges related to cultural variations, generational shifts, and the dynamic nature of workplace expectations are also discussed. Practical implications for HR managers and organizational leaders include designing jobs that enhance motivator satisfaction, conducting hygiene audits, and implementing transparent, employee-centric policies. The article concludes that integrating Herzberg’s insights into retention strategies can help organizations create a motivated and stable workforce, thereby sustaining competitive advantage in an evolving global business environment.